Identity Crisis in Adolescents Experienced by the Main Female Character in Moxie Movie - Dewi, Yunita Kumala; Asmarani, Ratna (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
AbstractMoxie is a movie directed by Amy Poehler based on the novel of the same name, written by Jennifer Mathieu. This movie is about the main female character, a young girl called Vivian, who is in the process of finding her identity. This paper aims to analyze the identity crisis experienced by Vivian and shows the reader that an identity crisis is common in adolescence. This thesis uses Erik Erikson's concepts on identity crisis The focus is on the symptoms, causes, effects, and solution of identity crisis. The writer uses library research to collect relevant data and qualitative research to analyze the data. After conducting the analysis, the results show that Vivian faces various event at school and home. She experiences role confusion, discomfort, and emotional uncertainty, meaning that she experiences an identity crisis that usually occurs in adolescents as a transition process from childhood to adulthood. However, she finally can overcome her identity crisis.